Victim-survivors’ views on and expectations for the criminalisation of coercive control in Australia: Findings from a national survey - FItz-Gibbon, Kate; Reeves, Ellen; Meyer, Silke; Walklate, Sandra (Monash Gender and Family Violence Prevention Centre, Monash University, 2023)
There has been unprecedented attention at the national and state level over the last decade on improving and reforming responses to domestic, family and sexual violence across Australia. The findings of recent national and state level reviews have revealed the significant limitations in legal responses to domestic and family violence, and the need to develop new policies and practices to better respond to perpetrators and ensure the safety of victim-survivors. Within this reform context, and in the wake of several high-profile intimate partner homicide cases, there has been increasing debate surrounding the need to criminalise coercive and controlling behaviours. This study originated from a recognition that debates surrounding legal responses to coercive control were largely occurring across Australia and elsewhere internationally in the absence of any significant evidence as to the views and experiences of victim-survivors of domestic and family violence. Presenting the findings of a national survey of 1,261 victim-survivors of coercive control, this study significantly advances Australian understandings of victim-survivors views on the criminalisation of coercive control. This study found that 87.5 per cent of survey participants believe coercive control should be a criminal offence including 91 per cent of female identifying survey participants and 69.5 per cent of male identifying survey participants. 86.67 per cent of LGBTQA+ participants; 85 per cent of First Nations participants believed coercive control should be a criminal offence and 87 per cent of participants with disability believed coercive control should be a criminal offence. Responses received from victim-survivors were remarkably consistent. 93 per cent thought that criminalisation would improve community awareness of coercive control. Mirroring the wider survey sample, victim-survivors from LGBTQA+ communities, First Nations victim-survivors, and victimsurvivors living with a disability also consistently identified improved community ...